Diseño de un modelo matemático para la calificación de clientes morosos en una entidad comercial mediante las metodologías de árboles de decisión, análisis discriminante y regresión logística - Ruiz López, Hugo Renán (2017)
In the present work, a mathematical model is designed for the qualification of delinquent clients in order to optimize the management of collections in a commercial enterprise. To do this we developed two parametric models, Discriminant Analysis and Logistic Regression and a non-parametric model, the Decision Trees. It determines the stability of each model, its power of discrimination and finally establish which of the methodologies allows better optimization of collection management.